2000
DOI: 10.1149/1.1394091
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chromate Conversion Coatings on Al-Cu-Mg Intermetallic Compounds and Alloys

Abstract: "Accelerated" chromate conversion coating (CCC) formulations are distinguished among all CCC types by the fact that they utilize a special chemical additive to increase coating weight, 1 or increase the rate of the film forming Cr VI to Cr III reduction reaction. 2 Ostensibly, accelerated CCCs are used on corrosion-prone Al-Cu-Mg and AlZn-Mg-Cu alloys to ensure maximum protection. 3 Ferricyanide [Fe(CN) 6 3Ϫ ] has been used as an accelerant in commercial CCC formulations since the 1960s. 1 Despite the long his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 13 publications
7
64
2
Order By: Relevance
“…McGovern et al studied the formation of chromate conversion coatings on copper-containing aluminum alloys. [19] The research obtained a similar result with Skeldon et al When the content of copper increased, the formation rate of chromate conversion coatings slowed down. Although the researches mentioned in the preceding texts studied the influences of alloying, all the researched alloying elements were metals.…”
Section: Introductionsupporting
confidence: 73%
“…McGovern et al studied the formation of chromate conversion coatings on copper-containing aluminum alloys. [19] The research obtained a similar result with Skeldon et al When the content of copper increased, the formation rate of chromate conversion coatings slowed down. Although the researches mentioned in the preceding texts studied the influences of alloying, all the researched alloying elements were metals.…”
Section: Introductionsupporting
confidence: 73%
“…18,21,22 McGovern et al 21 concluded that the deposition rate on Mg-containing intermetallics slowed with increased Cu content due to adsorption of cyanide on the Cu-rich sites. The cyanide is derived from potassium ferricyanide that is added to commercial CCC bath formulations to accelerate the coating deposition process on aluminum.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, these chemicals present environmental problems. 1,2 To overcome this problem, extensive work has been undertaken in the literature, either through wet chemistry and/or through plasma treatment.…”
Section: Introductionmentioning
confidence: 99%